2017
DOI: 10.9745/ghsp-d-16-00410
|View full text |Cite|
|
Sign up to set email alerts
|

Improving Adherence to Essential Birth Practices Using the WHO Safe Childbirth Checklist With Peer Coaching: Experience From 60 Public Health Facilities in Uttar Pradesh, India

Abstract: Implementation of the WHO Safe Childbirth Checklist with peer coaching resulted in >90% adherence to 35 of 39 essential birth practices among birth attendants after 8 months, but adherence to some practices was lower when the coach was absent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
69
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(76 citation statements)
references
References 30 publications
6
69
0
Order By: Relevance
“…The trial showed an improvement in performance of these practices after only 2 months of the intervention 34 . These results suggest that the BetterBirth strategy of implementing the WHO SCC with coaching can be a method for achieving change in facility-based childbirth care 34 .…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…The trial showed an improvement in performance of these practices after only 2 months of the intervention 34 . These results suggest that the BetterBirth strategy of implementing the WHO SCC with coaching can be a method for achieving change in facility-based childbirth care 34 .…”
Section: Resultsmentioning
confidence: 87%
“…The trial showed an improvement in performance of these practices after only 2 months of the intervention 34 . These results suggest that the BetterBirth strategy of implementing the WHO SCC with coaching can be a method for achieving change in facility-based childbirth care 34 . However, further research is needed to clarify which aspects of coaching-centered interventions contribute most to increasing use and sustainability of the SCC and to consistent adoption of essential birth practices.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Using the OAMS framework also enabled tracking change in the types of barriers coaches faced over time. The percent of nonadherence attributable to motivation barriers decreased during the 8 months of the study—a change consistent with the focus of coaching on individual behavior change through observation, motivation, and feedback rather than on clinical skills mentoring . Similarly, the percent of EBP nonadherence attributable to opportunity barriers decreased over time, whereas the percent attributable to supplies did not.…”
Section: Discussionmentioning
confidence: 59%
“…In conclusion, integration of the OAMS behavior change framework into the coaching‐based implementation of the WHO SCC was acceptable, feasible and facilitated coaches’ correct categorization of barriers and their development of appropriately responsive strategies to address these barriers. The use of OAMS‐informed coaching was associated with an increase in adherence to EBPs . By contrast, supervision—as currently delivered in some settings—is not always associated with higher quality of care .…”
Section: Discussionmentioning
confidence: 93%